PENGARUH TEHNIK AKUPRESUR TERHADAP PENURUNAN TINGKAT NYERI PADA SISWI KELAS X YANG MENGALAMI DISMENORE PRIMER DI SMA NEG. 2 KOTA SUNGAI PENUH TAHUN 2015 - Yati, Sarni (Menara Ilmu, 2019)
Painful is an unpleasant sensory and emotional experience that has relationship with tissue damage actually or ppotentially. In overcome primary dysmenorrhea, many people do not think to do acupressure tehnique to degrade painful in primary dysmenorrhea,but they only use farmakologi medication. The aim of this research is to know the influence of acupressure tehnique to the painful level regradation of primary dysmenorrhea in class X MAN 2 Batusangkar in 2012. This research design was quasy experiment with one group pre-post test design approach. Population in this research is entire of schoolgirl in class X MAN 2 Batusangkar. This research used 10 Juny-26 July 2012. With the taking technique the sample used purposive sampling with 31 respondents. The data collecting used observation pieces with painful measurement scale. Then the data was proccesed with SPSS. To use analisys univariat and bivariat.The result of this research showed that from 31 respondents with primary dismenore, before acupressure tehnique experienced light painful ( 36%), medium painful ( 48%) and heavy painful (16%).After conducted acupressure tehnique which not pain ( 29%), experienced of light painful (32%),medium painful (32%) and heavy painful ( 6%). From the statistic test result, it was got significant 0.000 so Ho rejected. It can be concluded that there was significant difference between painful before and after acupressure technique was done. Based on this research can be concluded that acupressure technique was effective to degrade painful of primary dysmenorrhea. Researcher suggest to the schoolgirl of primary dysmenorrhea so that can conduct acupressure technique if experiencing of painful, and to the health officer can execute acupressure technique to minimization painful. Reference 29 ( 2001-2011) Keyword : Acupressure technique, painful level, primary dysmenorrhea